2021
DOI: 10.21511/bbs.16(3).2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of job autonomy and its effect on work engagement: A study of the banking industry in Nigeria

Abstract: An individual’s ability to exercise freedom in how he/she plans his/her work is referred to as job autonomy, and this is associated with many positive work outcomes. Work engagement is a positive work outcome that many organizations desire to see in their employees due to its impact on productivity. This study was carried out to examine the extent of job autonomy in ensuring that banking industry employees in Nigeria attain a certain level of work engagement. The study used a mixed investigation method, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Category 4 banks in Indonesia are large banks with large income and assets. With the specified qualifications, it is expected to represent objectively the actual http://dx.doi.org/10.21511/bbs.17 (1).2022.15…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Category 4 banks in Indonesia are large banks with large income and assets. With the specified qualifications, it is expected to represent objectively the actual http://dx.doi.org/10.21511/bbs.17 (1).2022.15…”
Section: Methodsmentioning
confidence: 99%
“…It is important to create opportunities for employees to establish good relations with the work environment and create a comfortable atmosphere for employees to work (Judeh, 2021). When employees are comfortable, they will be more active at work (Adeniji et al, 2021).…”
Section: Employee Engagementmentioning
confidence: 99%
“…There have been few studies outside Malaysia on understanding the effect of job autonomy and job satisfaction in the workplace (Sarinah et al, 2018;Malinowska et al, 2018;Muecke & Greenwald, 2020;Ade-Adeniji et al, 2021). These findings concluded that, job autonomy is a key predictor towards job satisfaction.…”
Section: Statement Of Problemmentioning
confidence: 98%
“…Job autonomy is always described as an individual's amount of independence in determining how work is done. This is especially include making decisions in carrying out their jobs (Ade-Adeniji et al, 2021), where having flexibility and discretion to accomplish their duties and responsibilities are crucial (Dodd & Ganster, 1996;Lin & Ping, 2016).…”
Section: Statement Of Problemmentioning
confidence: 99%
“…Job autonomy and employee engagement are significantly related. Job autonomy is a major determinant of employee engagement and is positively correlated with employee engagement levels (Zhang et al, 2017;Kenyi and John, 2020;Ade-Adeniji et al, 2021). The pharmaceutical industry would therefore have a keen interest in (re)evaluating job autonomy interventions where employees are able to carry out the work using their own initiative or judgment and have opportunities for independence and creative freedom (Thisera and Wijesundara, 2020;Tummers et al, 2018).…”
Section: Practical Implicationmentioning
confidence: 99%